A theoretical framework of chain management - Jon Hanf; Kirsti Dautzenberg (Journal on Chain and Network Science, 2006)
Strictly coordinated chain organisations have been in place in the agri-food business for many years. The majority of them are collaborative. These organisations have a pyramidal-hierarchical structure. A focal firm, which is centrally located, coordinates the network firms in a hierarchical style. Our paper aims to develop a managerial framework for networks, and we address cooperation as well as coordination. Gulati et al. (2005) conclude that even though cooperation may be achieved, i.e., the interests of the individual actors are aligned, coordination problems may persist. Thus, both the alignment of interests and the alignment of actions must be simultaneously achieved to create a successful partnership; they can be viewed as two sides of the same coin. Duysters et al. (2004) have shown that the management of alliances must be analysed on three levels: the firm, dyadic, and network levels. We have therefore combined the aspects of cooperation and coordination with these three levels. Because the focus of our paper is on the development of a theoretical chain management concept, we applied this concept to a case study. We are aware that this is not empirical evidence, but nonetheless it confirmed our findings. The case of a supply chain network of a German premium pasta manufacturer showed that the combination of cooperation and coordination with a differentiated view of the various network levels corresponds with the demands of real business life.
Keywords: 630; food chain management; cooperation; coordination; network levels